PERDAGANGAN UBIKAYU INDONESIA DI PASAR DUNIA (INDONESIA CASSAVA TRADE IN WORLD MARKET) - Asriani, Putri Suci (Jurnal AGRISEP, 2010)
There are lack of information andmisunderstanding, amongeconomic agents in agriculture farming system related to cassava potencies as food, feed, and industrial resources in agribusiness system. There are, among others, due to assymetric information system for economic potential of cassava marketing system (export and domestic market) in Indonesia, as well as, the information of production and potencies of cassava market in Indonesia, export and domestic market.  Economic strategic to develop strive the cassava productivity is feasible to fulfill export and domestic requirement. Information in production allocation  and marketing system for export and domesti consumption of cassava will be useful to design strategies for the product development in order to support food security.